2017
DOI: 10.1016/s1875-5372(17)30188-1
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Synthesis of Polycrystalline Ti 3 AlC 2 and Its Sintering Behavior

Abstract: A method for fabrication of ternary compound Ti3AlC2 powder by pressureless calcining (PC) technique was developed. Powders of Ti, Al and TiC were mixed as staring materials. The effects of calcining temperature and aluminum content on the purity of Ti3AlC2 were discussed. The reaction mechanism and the microstructure evolution of Ti3AlC2 prepared at different temperatures were investigated by X-ray diffraction, field emission scanning electron microscopy and high resolution transmission electron microscopy. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Figure S4 shows SEM images of the initial MAX phase powder sample with coexisting single-crystalline and polycrystalline particles. This mixture of single- and polycrystalline grains is formed by the high-temperature pressure-less sintering and subsequent milling of the green body in the synthesis process for Ti 3 AlC 2 . Polycrystalline grains can be distinguished by different single-crystalline grains connected to each other with different c -lattice orientations by weak grain boundaries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure S4 shows SEM images of the initial MAX phase powder sample with coexisting single-crystalline and polycrystalline particles. This mixture of single- and polycrystalline grains is formed by the high-temperature pressure-less sintering and subsequent milling of the green body in the synthesis process for Ti 3 AlC 2 . Polycrystalline grains can be distinguished by different single-crystalline grains connected to each other with different c -lattice orientations by weak grain boundaries.…”
Section: Resultsmentioning
confidence: 99%
“…This mixture of single-and polycrystalline grains is formed by the high-temperature pressure-less sintering and subsequent milling of the green body in the synthesis process for Ti 3 AlC 2 . 33 Polycrystalline grains can be distinguished by different single-crystalline grains connected to each other with different c-lattice orientations by weak grain boundaries. Void structures were also formed during the synthesis of the MAX phase (Figure S5).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Copper powder (99.5%, ≤45 μm, Sinopharm Chemical Reagent Co., Ltd. Shanghai, China) and Ti 3 AlC 2 powder (99.2%, ~5 μm, for details on synthesis process, see [27]) were mixed for 3 h with a constant Cu/Ti 3 AlC 2 volume ratio of 80:20. The mixture was put into a high strength graphite mold.…”
Section: Methodsmentioning
confidence: 99%
“…It may be noted that the starting powders are elemental Ti, Al, carbon, or compounds such as Al 4 C 3 , TiC, etc. All the above‐specified (Table 1) approaches illustrate that the synthesis and sintering of Ti 3 AlC 2 in bulk and dense form need pressure in the range 25–50 MPa, temperature 1400°C–1600°C, and duration 30 min–16 h 2–7,9–12 . It is observed that the additional phase of TiC presents along with Ti 3 AlC 2 3–7,9,12 .…”
Section: Introductionmentioning
confidence: 94%
“…The starting raw materials, processing methods, experimental parameters, phases present, density, and mechanical properties of Ti 3 AlC 2 are given in Table 1 2–12 . It may be noted that the starting powders are elemental Ti, Al, carbon, or compounds such as Al 4 C 3 , TiC, etc.…”
Section: Introductionmentioning
confidence: 99%